The Meaning of 'Bread' in John 6:25-59 - Hanna Levina Goei (English Language and Education Spectrum, 2023)
The use of a term to mark certain objects is an interesting topic. The reason for this is because there is a separate intention that the speaker wants to convey. This study is a study that focuses on the symbolic meaning of bread in the Gospel of John 6:25-59. The purpose of this study is to identify the depiction of bread in the passage. This study utilizes the theory of symbolism and data collection using note-taking technique. The results of this study found 1) there is a correlation between past social conditions and the use of the term bread, 2) there are two groups of uses of bread to describe the spiritual and physical needs of humans 3) bread is a symbolism of fulfillment and mortality 4) bread is a symbolism of the Lord Jesus Christ and the giver of eternal life 5) the implications of the use of bread symbolism can help readers to distinguish between mortal and eternal bread, as well as understand the coming and person of the Lord Jesus Christ in this passage.